Effects of temporal cueing on residual visual discrimination in blindsight. - Kentridge, R; Heywood, C; Weiskrantz, L (1999)
We tested the ability of a blindsight patient, GY, to identify in which of two locations a target was presented in a spatial two-alternative forced choice paradigm (spatial 2AFC). On each trial the subject was asked to make a second manual response indicating whether he had had any awareness of an event occurring during the trial. A cue, presented at the fixation location, could signal the 0.4 s period over which the target appeared within the 10 s duration of each trial. Targets of three contrasts, 93, 43 and 22% were used. We found that GY's ability to discriminate the location of targets in his blind field remained significantly above chance, with and without cueing, for each contrast. Cueing, did, however, significantly improve his performance for low contrast targets. When he performed a similar task with near threshold contrast targets in his spared visual field his discrimination was at chance unless the presentation of targets was cued, despite his reporting more awareness for these stimuli than he did for low-contrast stimuli in his blind field. These results are compared with those previously reported in monkeys who received lesions to their visual cortices as infants or adults. We conclude that (1) GY's blindsight is qualitatively different from near-threshold normal vision. (2) In common with infant-lesioned monkeys his blindsight remains even in the absence of temporal cues. (3) Residual vision is subject to modulation by attentional processes, or arousal, associated with temporal cueing.